2004
DOI: 10.2105/ajph.94.7.1186
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of HIV Prevention Counseling by Physicians at HIV Medical Care Settings in 4 US Cities

Abstract: Intervention strategies with physicians should be developed to overcome barriers to providing counseling to HIV-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 35 publications
(28 reference statements)
5
59
1
1
Order By: Relevance
“…These indicate that patient's learned the role of HAART than what they knew at the beginning. These are in agreement with Korb-Savoldelli et al and Metsch et al demonstrating that EI on medication instructions positively modify patient's beliefs which in turn can lead to a change in patient's medication adherence behavior [34,35]. During this study, ICG patients received PIL on antiretroviral drugs.…”
Section: Among Our Icg Patients We Found That Impact Of Ei On Overallsupporting
confidence: 91%
“…These indicate that patient's learned the role of HAART than what they knew at the beginning. These are in agreement with Korb-Savoldelli et al and Metsch et al demonstrating that EI on medication instructions positively modify patient's beliefs which in turn can lead to a change in patient's medication adherence behavior [34,35]. During this study, ICG patients received PIL on antiretroviral drugs.…”
Section: Among Our Icg Patients We Found That Impact Of Ei On Overallsupporting
confidence: 91%
“…DL-identified MSM rated the trustworthiness of information from their health care provider higher than information from local AIDS organizations or the CDC. Patients often consider their health care providers to be trusted sources of health information (David and Boldt, 1980), but many providers fail to address HIV risk and its prevention during clinical encounters (Dodge et al, 2001;Gerbert, Maguire, and Coates, 1990;Margolis, Wolitski, Parsons, and Gomez, 2001;Marks et al, 2002;Metsch et al, 2004;Wenrich, Carline, Curtis, Paauw, and Ramsey, 1996). Brief patient-provider interactions are feasible, generally acceptable to patients, and can motivate patients to reduce HIV risk (Dodge et al, 2001;Gerbert et al, 1990;Richardson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This provides an opportunity to target secondary prevention with advantages of repeated contacts over time, establishment of trusted relationships, and using health care providers as expert sources of health information. In a study of physician-delivered HIV prevention for positives in 4 US cities, 14% counseled established patients and 60% counseled newly diagnosed HIV patients (Metsch et al, 2004). Counseling was more likely if providers reported that there was sufficient time and had familiarity with treatment guidelines.…”
Section: Bundled "Prevention For Positives"mentioning
confidence: 99%